Adverse childhood experiences predict anxiety during postpartum and early childhood parenting - Chelsea Walker-Mao; Charlotte V. Farewell; Sarah Nagle-Yang; Sarah Blackwell; Jenn A. Leiferman (Taylor & Francis Group, 2024)
Perinatal anxiety disorders (PAD) affect one in five pregnant/postpartum people and are associated with adverse maternal and child health outcomes. Effective treatment and prevention rely on early identification and management of risk factors. Our study fills a gap in literature about how maternal adverse childhood experiences (ACEs) relate to PAD during and beyond the postpartum period. Using longitudinal data from a population-based sample of mothers in Colorado, USA (N = 1116), we evaluated whether maternal ACEs predicted self-reported anxiety symptoms, measured six times between 3 and 36 months postpartum. A mixed mean model of anxiety was fit with ACEs as the predictor and maternal age, race, ethnicity, education, marital status, and parity as covariates. Controlling for sociodemographic covariates, mothers reporting four or more ACEs had significantly higher levels of anxiety than those reporting less than four ACEs (b = 0.84, 95% CI (0.53, 1.15), p<.001) over the three-year period. Mothers of younger age at time of birth (25-34 years vs. <24 years: b=-0.54, 95% CI (-1.00, −0.08), p=.02) and non-Hispanic ethnicity (b = 0.47, 95% CI (0.09, 0.85), p=.01) were also found to have higher anxiety over this period. Our findings support screening for and addressing maternal ACEs early in obstetric care and well-child visits through trauma-informed, strengths-based approaches that promote maternal, child, and intergenerational well-being.